Sikap terhadap wang bertindak sebagai pembolehubah moderator dalam perhubungan antara kepuasan kerja dan keinginan untuk berhenti secara sukarela - Wati, Kuching (2008)
This study was conducted to examine the moderating role of attitudes toward money in the relationship between job satisfaction and turnover. The outcomes of hierarchical regression analysis showed that interaction between attitudes toward money and intrinsic job satisfaction, and interaction between attitudes toward money and intrinsic job satisfaction significantly correlated with turnover. These research finding explain hat attitude toward money plays full moderating role in the job satisfaction model of the studied organization.